All Kinds of Friends, Even Green! - Senisi, Ellen B. (USA, 2002)
In a school assignment, seven-year-old Moses, who has spina bifida and uses a wheelchair, reflects that his neighbour's disabled iguana resembles him because they both have figured out how to get where they want to be in different ways than those around them.
Keywords: People with disabilities / Wheelchairs / Iguanas; Juvenile Fiction; Schools / Spina bifida